PENGARUH SUPERVISI TERHADAP KELENGKAPAN DOKUMENTASI ASUHAN KEPERAWATAN DI RUANGAN NON BEDAH - Rezkiki, Fitrianola; Ilfa, Annisa (Universitas Fort De Kock Bukittinggi, 2018)
The lack of complete documentation of nursing care (58%) affects the achievement of quality health care in hospitals. Seeing the benefits and importance of documenting nursing, it is necessary to have control over the documentation of nursing care carried out by nurses, namely by the existence of supervision activities. The purpose of the study was to improve the completeness of nursing care documentation through supervision in a Non-Surgical Room. This study used a pre-experimental design with a design (One-Group Pretest-Posttest design). The sampling technique used purposive sampling as many as 15 nurses. Data was analyzed using Paired T-Ttest with a value of p = 0.00. The results showed that the average completeness of nursing care documentation before supervision was 70.27%. The average completeness of nursing care documentation after supervision of 82.27%. There is a significant effect of supervision on the completeness of nursing care documentation with a mean value of -12,000 and p = 0.00. The conclusions from the study indicate the influence of completeness of nursing care documentation before and after supervision. It is recommended that the head of the room make effective the supervision of the room by making a schedule of routine supervision of the head of the room known to managerial nursing. Keywords: supevision, documentation of nursing care